Neurofibromatosis Type 1 Vasculopathy Presenting as Branch Retinal Vein Occlusion: Case Report and Review of the Literature - Zeydanli, Ece Ozdemir; Ozdek, Sengul (Turk oftalmoloji gazetesi, 2023)
Systemic vascular occlusive disease associated with neurofibromatosis type 1 (NF1) has been reported in the aortic, cerebral, renal, celiac, and mesenteric vessels and is referred to as NF1 vasculopathy. Although retinal vascular involvement in patients with NF1 usually manifests as retinal capillary hemangiomatosis, a few cases of NF1 with retinal vascular occlusive disease have also been described. Here, we report a 2-year-old girl with NF1 who presented with branch retinal vein occlusion and peripheral retinal ischemia secondary to NF1. This case demonstrates that NF1-related retinal occlusive vasculopathy may occur in very young patients and that detailed fundus examination with fluorescein angiography is necessary in all patients with NF1.